Nutrition Awareness among Middle School Students and its relation to some Variables (Journal of the College of Education for Women, 2018)
The aim of the study was to identify the nutritional awareness of middle school students and its relation to some variables of the sample of the research according to the gender variable (male and female), the variable type of family and the variable achievement of the parents. The descriptive approach was adopted and the sample of the study consisted of (795) male and female students who were selected by the random stratified method. The research tool was prepared based on the literature and previous studies. The food awareness measure in its final form was (25) after the data collection was processed using the appropriate statistical methods and the most important results that. Research1- Middle school students enjoy a good level of food awareness.There are no statistically significant differences depending on gender 3. Lack of interaction between food awareness and variable family typeThere are no statistically significant differences between the parents' achievement of the study sample in the measure of nutritional awareness. found that the most important source of the demand for their food information from the Internet (World Wide Web) in the first rank and then occupied only And then occupied the family and friends in the light of the results reached by the researchers a number of recommendations and proposals from them.